SECULAR SPIRITUALITY AS AN ANTIDOTE TO RELIGIOUS FUNDAMENTALISM - Dominic George (Journal of Dharma, 1990)
The term ’secular spirituality’ might sound a bit odd and contradictory at first sight. But we have used it here with some deliberation, knowing full well that there are some problems with this terminology. We have considered alternatives like ’this-worldly spirituality’ and ’reality-contacted spirituality’ etc, which also could have served our purpose. But we have stuck to the term ’secular spirituality’ for some reasons of our own which will become clear,we hope, in the course of this exposition. The term ’religious fundamentalism’ is taken to be well understood by most people in India without the need for elaborate explanations. Basi- cally, there is, in a religious fundamentalist, an attitude of rigid and intole- rantorthodoxy, an attitude of historical traditionalism, an attitude of revivalist fervour that opposes ’reform’, an attitude of inflexible certitudes, an attitude of crusading opposition to all views and heritages other than that of the fundamentalist. In this context, it may be said in passing that there are ’secular fundamentalists’ as well as ’religious fundamentalists’, both revealing very similar characteristic and motivational patterns. The basis of the fundamentalism of the ’secular fundamentalist’, is a secular ideology which he clings to with rigidity and fanaticism. The ’religious fundamentalist’, on the other hand, roots himself in some kind of a ’religious ideology: